The Life of/in Nature. From Hegel to British Idealism and Its Twentieth-Century Afterlives - Battistoni, Giulia (ETHICS IN PROGRESS, 2025)
This essay traces the philosophical development of the concept of organic life and nature from Hegel’s Philosophy of Nature through British Idealism to the twentieth-century thought of Alfred North Whitehead and Hans Jonas. It highlights how Hegel’s idea of the organism as a self-producing, purposive unity influenced later thinkers, directly or indirectly, shaping views of nature as inherently processual, relational, and teleological. By uncovering the Hegelian echoes in British Idealism and beyond, the essay argues for the continuing relevance of speculative conceptions of life and nature. This reconstruction offers new insights into contemporary philosophical biology and environmental ethics, suggesting that the categories of organism, purposiveness, and selfhood remain vital for rethinking the place of life within nature today.